Penegakan Hukum terhadap Tindak Pidana Militer Desersi di Wilayah Hukum Pengadilan Militer II-09 Bandung Ditinjau dari Aspek Hukum Pidana Militer - Heru Rustaman; Dini Dewi Heniarti (UNISBA Press, 2024)
Abstract. Desertion is a criminal offense caused by the absence of a military person without the permission of his immediate superior, at a place and time determined by the service, by running away from the unit and leaving military service, or leaving by leaving, running away without permission. Desertion is a purely military crime regulated in article 87 of the Military Criminal Code. In the jurisdiction of Military Court II-09 Bandung in the period from 2021 to 2023 there were 167 (one hundred and sixty) dissent cases. When compared with other crimes, desertion is always the highest crime committed. The formulation of the problem in this research includes: How is law enforcement against the military crime of desertion in the jurisdiction of Military Court II-09 Bandung viewed from the Military Criminal Law Aspect and what are the causes of the military crime of desertion in the jurisdiction of Military Court II-09 Bandung. The goal is to find out what has been described in the formula. The research method used is a normative juridical method with non-doctrinal qualitative methods. The results of this research are that law enforcement regarding the military criminal act of desertion in the jurisdiction of Military Court II-09 Bandung is carried out based on the resolution of desertion cases in general, starting from investigation, prosecution, examination at trial, and execution. It's just that the criminal procedure legal process in a desertion case if the defendant does not appear at the trial is known as a trialIn Absence. However, if the defendant is present during the trial, the court can decide the trial by Niet Ontvankelijke (N.O). And the factors that cause the military criminal act of desertion in the jurisdiction of Military Court II-09 Bandung consist of various factors, including: Lifestyle, Mentality, Leadership Role and Work Environment Situation, Duties and Service Placements That Do Not Meet Expectations, Household Problems and Burden Life. Abstrak. Disersi merupakan suatu tindak pidana yang dikarenakan tidak beradanya seorang militer tanpa izin atasannya langsung, pada suatu tempat dan waktu yang sudah ditentukan oleh dinas, dengan lari dari kesatuan dan meninggalkan dinas kemiliteran, atau keluar dengan cara pergi, melarikan diri tanpa ijin. Desersi merupakan suatu tindak pidana militer murni yang diatur dalam pasal 87 Kitab Undang-Undang Hukum Pidana Militer. Di wilayah hukum Pengadilan Militer II-09 Bandung dalam kurun waktu dari tahun 2021 hingga 2023 terdapat 167 (serratus enam puluh) perkara disersi. Jika dibandingkan dengan tindak pidana lain, desersi selalu menjadi tindak pidana yang paling tinggi dilakukan. Rumusan masalah dalam penelitian ini meliputi: Bagaimana penegakan hukum terhadap tindak pidana militer desersi di wilayah hukum Pengadilan Militer II-09 Bandung ditinjau dari Aspek Hukum Pidana Militer serta Apa penyebab terjadinya tindak pidana militer disersi di wilayah hukum Pengadilan Militer II-09 Bandung. Tujuannya adalah untuk mengetahui apa yang telah diuraikan pada rumusan tersebut. Metode penelitian yang digunakan adalah metode yuridis normatif dengan non-doktrinal kualitaif. Hasil dari penelitian ini yaitu Penegakan hukum terhadap tindak pidana militer desersi di wilayah hukum Pengadilan Militer II-09 Bandung yaitu dilaksanakan berdasarkan penyelesaian perkara desersi secara umum, dimulai dari Penyidikan, Penuntutan, pemeriksaan di persidangan, dan eksekusi. Hanya saja proses hukum acara pidana dalam perkara desersi jika terdakwa nya tidak hadir di persidangan dikenal dengan persidangan In Absensia. Tetapi apabila pada proses persidangan Terdakwa hadir, maka pengadilan dapat memutus sidang secara Niet Ontvankelijke (N.O). Serta Faktor penyebab tindak pidana militer desersi di wilayah hukum Pengadilan Militer II-09 Bandung terdiri dari berbagai macam faktor antara lain: Gaya Hidup, Mental, Peran Kepemimpinan dan Situasi Lingkungan Kerja, Tugas dan Penempatan Dinas Yang Tidak Sesuai Harapan, Persaoalan Rumah Tangga dan Beban Hidup